Development of Tutorial Video Media for Traditional Dance Materials in Cultural Arts Lessons - Hafiidha Gusti Haryani; Elida Elida (International Journal of Educational Dynamics, 2021)
This study aims to analyze the development process, the level of validity, the level of practicality, and the level of effectiveness of developing video tutorial media for traditional dance materials in Cultural Arts lessons in Junior High School (JHS). There are three analytical techniques used to process data from product development, namely content analysis, descriptive analysis, and t-test analysis. The results of this study show that the development of video tutorial media in traditional dance masters uses the Research & Development (R & D) method with a model of development analysis, design, development, implementation, evaluate (ADDIE ). The results of the overall student response showed a very backward response because it was used without obstacles which had fatal consequences to the use of video tutorial media in traditional dance material, namely andun dance in cultural arts lessons. The results of the overall student response showed a very reversed response because it was used without obstacles which had fatal consequences to the use of medial video tutorials on traditional dance materials, namely andun dance in cultural arts lessons. The results of the questionnaire based on the effectiveness test on the development of video tutorial media found that many students like cultural arts lessons, students are more interested and motivated in learning by using video tutorial media, students tend to be active in learning and their curiosity increases. It can also be seen from the observation sheet that students' interest in learning with video tutorial media has increased.